Masculinity and prostitution continuum: self-representations of female prostitution “clients” - Ranea-Triviño, Beatriz (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2022)
This article focuses on the approach to the male demand for female prostitution in the Spanish context and it analyzes how the periodicity of prostitution consumption influences the perception and subjective identification of men with respect to prostitution. A difference has been established between the typology of eventual clients who do not identify with the consumption of prostitution, and therefore, in their self-representation there is a disidentification with respect to this practice. And, on the other hand, regular customers who perceive prostitution as a part of their identity and as a relatively everyday element.